BUILDING POLITICAL CIVILITY FOR PEOPLE WITH DISABILITIES BY COUNTRY - Fenty Widya; Surizki Febrianto (International Conference On Law And Social Sciences, 2024)
For the equality of people with disabilities is very important for the state to run a civilized politics against Group Ini. Politics of civility can be defined as politics in the form of character or politics that has a good nature in carrying out the course of politics. Because politics is a basic right of every citizen of Indonesia which is a democratic country based on law. In order to build the politics of civility, Country must realize and know there is a group of disabilities in the order of society that must be fulfilled their rights, treated equally in the eyes of the law so that it needs awareness,civility to be able to treat them equally without discrimination then the thing that the state is doing is to have civility and ethical values in dealing with people with disabilities.The purpose of this study was to determine the extent to which the civility of the government as a stakeholder of power and policy in the fulfillment of political rights disability.This research uses empirical juridical methods, stages research methods are literature studies, interviews, field observations, focus group disscussion and analysis of state data in this case the government must have a character that upholds human rights and human values which is the value of civility that must be owned because the government is the main line and the forefront in this case the fulfillment of disability political rights in accordance with applicable laws.